2018
DOI: 10.1002/hbm.24048
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition in the face of emotion: Characterization of the spatial‐temporal dynamics that facilitate automatic emotion regulation

Abstract: Emotion regulation mediates socio-cognitive functions and is essential for interactions with others. The capacity to automatically inhibit responses to emotional stimuli is an important aspect of emotion regulation; the underlying neural mechanisms of this ability have been rarely investigated. Forty adults completed a Go/No-go task during magnetoencephalographic (MEG) recordings, where they responded rapidly to either a blue or purple frame which contained angry or happy faces. Subjects responded to the targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 67 publications
9
24
1
Order By: Relevance
“…We initially validated the modulatory influence on the behavioral level and in line with previous studies expected that subjects would tend to exhibit longer reaction times for negative stimuli and make more errors during the suppression of responses during positive stimuli (Albert et al, 2012; Hare et al, 2005; Liu et al, 2020; Putman et al, 2010; Schulz et al, 2007). Based on previous animal models and human neuroimaging studies we expected that dorsal striatal and lateral prefrontal regions would exhibit a general engagement during inhibitory control, while regions engaged in emotional and valence processing, specifically the amygdala, ventral striatum and orbitofrontal regions (Goldstein et al, 2007; Hare et al, 2005; Taylor et al, 2018) would exhibit emotional context-specific engagement during inhibitory control. Given the pivotal role of the fronto-striatal cicruits in inhibitory control and their sensitivity to emotional context (Chang et al, 2020; Christakou et al, 2004; Li and Sinha, 2008; Somerville et al, 2011), we further hypothesized that core regions of this circuitry would exhibit emotional context-sensitive modulations on the network level.…”
Section: Introductionmentioning
confidence: 99%
“…We initially validated the modulatory influence on the behavioral level and in line with previous studies expected that subjects would tend to exhibit longer reaction times for negative stimuli and make more errors during the suppression of responses during positive stimuli (Albert et al, 2012; Hare et al, 2005; Liu et al, 2020; Putman et al, 2010; Schulz et al, 2007). Based on previous animal models and human neuroimaging studies we expected that dorsal striatal and lateral prefrontal regions would exhibit a general engagement during inhibitory control, while regions engaged in emotional and valence processing, specifically the amygdala, ventral striatum and orbitofrontal regions (Goldstein et al, 2007; Hare et al, 2005; Taylor et al, 2018) would exhibit emotional context-specific engagement during inhibitory control. Given the pivotal role of the fronto-striatal cicruits in inhibitory control and their sensitivity to emotional context (Chang et al, 2020; Christakou et al, 2004; Li and Sinha, 2008; Somerville et al, 2011), we further hypothesized that core regions of this circuitry would exhibit emotional context-sensitive modulations on the network level.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, such a task can assess potential differences in N170 amplitude and latency responses to angry and happy faces across ASD and TD groups, as well as any behavioral differences on inhibitory control performance for angry and/or happy trials across groups. Studies have shown that emotional face stimuli can either (a) interrupt ongoing cognitively controlled tasks, effectively reducing attentional allocation to the given inhibitory control task resulting in reduced task performance scores ( Verbruggen and De Houwer, 2007 ; de Houwer and Tibboel, 2010 ), or (b) increase salience to the inhibitory control task, increasing the processing speed and possibly performance accuracy of the inhibitory stimuli ( Taylor et al, 2018 ). Determining the direction and degree of interaction between happy face stimuli, angry face stimuli and inhibitory stimuli in children with ASD compared to TD children would, therefore, be highly beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with the dual‐competition model suggesting that the impact of emotion on cognition depends on the arousal of the stimulus (Pessoa, ). Although emotion regulation is usually considered as an explicit and deliberate process (Gross, ) accumulating evidence shows that emotion regulation often operates on more automatic or implicit levels (Mauss, Bunge, & Gross, ; Gyurak, Gross, & Etkin, ; Koole & Rothermund, ; Urbain, Sato, Pang, & Taylor, ; Taylor et al, ). Automatic emotion regulation (AER) processes are frequently required in daily life, helping us prevent emotional context from interfering with the ongoing activities, for instance, by efficiently offsetting the impact of negative or unwanted emotional responses with minimal attentional resources (see Koole, Webb, & Sheeran, for a review).…”
Section: Introductionmentioning
confidence: 99%